Upregulation of Yin-Yang-1 Associates with Proliferation and Glutamine Metabolism in Esophageal Carcinoma. (20th March 2022) - Luo, Can; Chen, Xin; Bai, Yuting; Xu, Lei; Wang, Shuqi; Yao, Lihua; Guo, Xiaolan; Wang, Dongsheng; Zhong, Xiaowu
Abstract : Objective . To investigate the expression of Yin-Yang-1 (YY1) in esophageal carcinoma (ESCA) and its effect on glutamine metabolism in ESCA. Methods . The expression and roles of YY1 in ESCA were investigated using a series of bioinformatics databases and tools. The expression of YY1 between ESCA tissues with the corresponding adjacent tissues was validated using real-time PCR, western blot, and immunohistochemical staining method. Furthermore, the effects of YY1 on ESCC cell proliferation and migration were examined. The correlation between the YY1 and glutamine metabolism was evaluated by western blot. Results . YY1 gene was highly conserved in evolution and upregulated in ESCA tissues and ESCC cell lines (ECA109 and TE-1). In addition, YY1 may affect the level of immune cell infiltration and promote tumor cell immune escape. Functional enrichment analysis found that YY1 involved in many biological processes, such as cell division and glutathione and glutamine metabolism. After siRNA knockdown of YY1 in ECA109 and TE-1, the proliferation and the migration of ECA109 and TE-1 were suppressed. The glutamine consumption and glutamate production were significantly decreased. The protein expression of alanine-, serine-, cysteine-preferring transporter 2 (ASCT2), glutaminase (GLS), and glutamate dehydrogenase (GLUD1) was significantly downregulated. Conclusion . YY1 is highly expressed in ESCA and may promote glutamine metabolism of ESCC cells, indicating it may be as a diagnostic biomarker for ESCA.